SUDDEN NATURAL DEATH: AUTOPSY-BASED CROSS-SECTIONAL STUDY AT SCB MEDICAL COLLEGE, CUTTACK, ODISHA. - Chaman Kumar Bisoyi; Pati, Suryakanta; Dilip Kumar Mallick; Praveen Kumar Pradhan (Student’s Journal of Health Research Africa, 2024)
Background: Sudden natural death represents a critical area of medical and forensic investigation, encompassing instances where death occurs suddenly without preceding symptoms. Despite advancements in diagnostic techniques, sudden natural deaths continue to pose significant challenges, particularly in understanding their underlying causes and associated risk factors. The study aimed to determine the causes of sudden natural death and assess the epidemiological and sociodemographic parameters linked to it. Methods: A cross-sectional study was conducted. Data were collected from various sources including inquest reports, autopsy records, and histopathological examinations. Results: Among the 250 cases (35.87%) identified as sudden deaths, with males constituting 86% of the cases compared to females at 14%. The demographic distribution showed a predominance of Hindus (60%), followed by Muslims (30%) and Christians (10%). Geographically, approximately two-thirds of cases originated from rural areas. Cardiovascular disease emerged as the leading cause (40%), with myocardial infarction being the most prevalent subtype. Other significant causes included cerebrovascular accidents, pulmonary embolism, respiratory, gastrointestinal, and central nervous system causes. Conclusion: This study provides valuable insights into the demographics, place of occurrence, and causes of sudden natural deaths. Understanding these factors is crucial for implementing effective preventive strategies and improving access to timely medical care, particularly in rural and residential settings. Recommendations: Based on the findings, recommendations include the implementation of targeted preventive measures to address modifiable risk factors for cardiovascular disease, enhancing access to healthcare facilities in rural areas, and promoting awareness about the signs and symptoms of sudden natural death among the general population.